In-situ growth of N–TiO2 on delaminated N–Ti3C2 with highly strengthened photocatalytic activity. (8th June 2022) - Ding, Zhipeng; Sun, Mingxuan; Liu, Wenzhu; Meng, Xianglong; Zheng, Yongqiang; Sun, Wangbing; Zhou, Qinfeng
Abstract: Herein, a collection of N–TiO2 /delaminated N–Ti3 C2 (NTTx) composites is designed and synthesized by one-step calcination of NH4 Cl–Ti3 C2 precursors. The thermal decomposition of NH4 Cl not only serves as the gas template to make the delamination of Ti3 C2, but also acts as N source to for doping. As expected, the N–TiO2 nanoparticles uniformly anchor on the surface and interlayer of Ti3 C2 nanosheets with intimate contact. Both the photocatalytic degradation rate of Rh–B and photocatalytic nitrogen fixation experiments of NTT2 composites show higher performance than that of pure P25 and NTT0 under visible light irradiation. The strengthened photocatalytic activity is due to the decrease of band gap by N doping in TiO2 and excellent electrical conductivity of N–Ti3 C2, which leads to enhanced light response and photogenerated electron-hole separation, respectively. This study develops a new strategy to design efficient photocatalysts for degradation of contaminants and fixation of nitrogen. Graphical abstract: The N–TiO2 /delaminated N–Ti3 C2 composites are fabricated via a facile in-situ calcination of NH4 Cl–Ti3 C2 precursors and improved photocatalytic performance on pollutant degradation and nitrogen fixation is demonstrated. Image 1 Highlights: N–TiO2 /delaminated N–Ti3 C2 composites are fabricated by annealing NH4 Cl–Ti3 C2 . Decomposition of NH4 Cl acts as gas template for delamination and N source for doping. Improved activity on photocatalytic degradation and nitrogen fixation is confirmed. Synergic effect of N doping and delaminated Ti3 C2 contributes to the enhancement.